Dampak Perceraian Terhadap Psikologi Anak - Nabila Veronika; Pradana Chairy Azhar; Azri Ranuwaldy Sugma (Prodi Pendidikan IPS STKIP AL MAKSUM, 2022)
Impact of Divorce on Child Psychology. This study aims to: (1) describe the meaning of marriage and the purpose of marriage, (2) describe the causes of divorce, (3) describe changes in children's behavior after the divorce of their parents, (4) describe the roles and duties of parents as the main caregivers for relatives. Child psychology can change drastically because of pressure from family problems, namely divorce. The focus of this research is: What is the psychological state of children from divorced families? What is the impact of divorce on children's social environment? How do children cope with an incomplete family situation? This research uses descriptive qualitative method. The qualitative approach taken is qualitative with a case study approach. The subjects in this study amounted to 1 couple, using a purposive sampling technique, namely sampling where the researcher has determined the specified criteria, namely married couples who are divorced and have children.